Single chest drain is not inferior to double chest drain after robotic esophagectomy: a propensity score-matched analysis - Eckert, F.; Merboth, F.; Giehl-Brown, E.; Hasanovic, J.; Müssle, B.; Plodeck, V.; Richter, T.; Welsch, T.; Kahlert, C.; Fritzmann, J.; Distler, M.; Weitz, J.; et al. (Frontiers in Surgery, 2023)
Chest drain management has significant influence on postoperative recovery after robot-assisted minimally invasive esophagectomy (RAMIE). The use of chest drains increases postoperative pain by irritating intercostal nerves and hinders patients from early postoperative mobilization and recovery. To our knowledge, no study has investigated the use of two versus one chest intercostal drains after RAMIE.This retrospective cohort study evaluated patients undergoing elective RAMIE with gastric conduit pull-up and intrathoracic anastomosis. Patients were divided into two groups according to placement of one (11/2020 -08/2022) or two (08/2018 -11/2020) chest drains. Propensity score matching was performed in a 1:1 ratio and the incidences of overall and pulmonary complications, drainage-associated reinterventions, radiological diagnostics, analgesic use, and length of hospital stay were compared between single drain and double drain subgroups.During the study period, 194 patients underwent RAMIE. 22 patients were included after propensity score matching in the single and double chest drain subgroup, respectively. Time until removal of the last chest drain (POD 6.7 ± 4.4 vs. POD 9.4 ± 2.7, p = 0.004) and intensive care unit (ICU) stay (4.2 ± 5.1 days vs. 5.3 ± 3.5 days, p = 0.01) were significantly shorter in the single drain group. Overall, pulmonary complications, drainage-associated events, re-interventions, number of diagnostic imaging, analgetic use, and length of hospital stay were comparable between both groups.This study is the first to demonstrate safety of single-intercostal chest drain use, and at least non-inferiority to double chest drains in terms of perioperative complications after RAMIE.